Analysing Irony for Translation - Chakhachiro, Raymond (Meta, 2009)
AbstractThis paper investigates the question of whether the classifications and general descriptions of irony, as true as they may seem, are plausible enough for enquiries into areas such as translation. The generic and philosophical analysis criteria provided by the literary criticism, literary theory and pragmatic approaches hover around broad interpretive models of irony. These criteria are impractical for the analysis of irony for translation purposes, although the translation of irony relies essentially on interpretation and creative reformulation. This is particularly the case when dealing with typologically distant languages, such as Arabic and English, in a specific text-type. To be able to “work” with ironic texts there is a need for a more objective and applicable approach, which considers the identification of formal and rhetorical devices of ironic texts, hence a linguistic analysis that explains the communicative function of these devices at both the utterance and discourse structure levels.